Life Threatening Fatal Viruses groups: Biohazard and Biosafety - Yasir, Saif Jabbar; Al-Makhzoomy , Taghreed Abdul Kareem (Medical Science Journal for Advance Research, 2023)
Background: Viruses are one of the most serious risks to humanity, as seen by severe epidemics in history, and they have the ability to shut down governments, disrupt whole industries, and inflict immense human misery while spreading through communities, countryside, villages, and forests. Viruses have developed to the point that they are difficult to eradicate. This complexity occurs in dealing with viral diseases and is heightened by the virus's structural and genetic nature. They exist as autonomous beings, neither entirely dead nor completely alive. Furthermore, numerous lethal viral groups for people and animals are still prevalent in various parts of the world, and the most hazardous aspect of these viruses is that they do not react to therapy. And the most dangerous aspect of some viral groups is that they are transferred from animals to people and cause severe disease in both. Many viral diseases today lack effective vaccinations, and such viruses are characterized by the speed and severity of their infection, which spreads rapidly and kills quickly, needing significant preparation and several delicate therapies to combat them. As a result, they are potentially lethal and can be employed as weapons and assault agents in bioterrorism. .